2007
DOI: 10.1111/j.1365-2672.2007.03359.x
|View full text |Cite
|
Sign up to set email alerts
|

The Flavobacterium psychrophilum OmpA, an outer membrane glycoprotein, induces a humoral response in rainbow trout

Abstract: Aims:  The purpose of this study was to characterize OmpA, a major glycoprotein isolated from the membrane fraction of Flavobacterium psychrophilum, and to evaluate its potential as antigenic unit in a possible vaccine. Methods and Results:  The expression product of ompA is a 465‐amino‐acid protein precursor that contains a 21‐amino acid signal peptide and has overall homology (up to 60% identity) with similarly sized proteins of some bacteria belonging to the Flavobacteriaceae family. The carboxy‐terminal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 44 publications
(47 reference statements)
3
42
0
Order By: Relevance
“…Proteins separated by SDS-PAGE or by 2-D IEF/SDS-PAGE were electroblotted onto a nitrocellulose filter (Bio-Rad) using a Bio-Rad TransBlot electrophoretic transfer cell as specified by the manufacturer. The blots were blocked with 5 % BSA in PBS for 1 h at room temperature and then incubated for 1 h with anti-F. psychrophilum OmpA rabbit serum (Dumetz et al, 2007), with a pool of antisera (dilution 1 : 2000 in 0.05 % Tween 20 in PBS) collected from 20 healthy trout (generously given by Scott E. LaPatra, Clear Springs Foods, Inc., Buhl, Idaho, USA) or with a pool of antisera (dilution 1 : 1000 in 0.05 % Tween 20 in PBS) collected from 20 CWD-convalescent trout taken from an infected French farm. The washing steps were performed three times with PBS-Tween 20.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Proteins separated by SDS-PAGE or by 2-D IEF/SDS-PAGE were electroblotted onto a nitrocellulose filter (Bio-Rad) using a Bio-Rad TransBlot electrophoretic transfer cell as specified by the manufacturer. The blots were blocked with 5 % BSA in PBS for 1 h at room temperature and then incubated for 1 h with anti-F. psychrophilum OmpA rabbit serum (Dumetz et al, 2007), with a pool of antisera (dilution 1 : 2000 in 0.05 % Tween 20 in PBS) collected from 20 healthy trout (generously given by Scott E. LaPatra, Clear Springs Foods, Inc., Buhl, Idaho, USA) or with a pool of antisera (dilution 1 : 1000 in 0.05 % Tween 20 in PBS) collected from 20 CWD-convalescent trout taken from an infected French farm. The washing steps were performed three times with PBS-Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…Many of these properties are related to four short protein loops that emanate from the protein to the outside of the cell (for a review see Smith et al, 2007). Although the N-terminal amino acid sequence of F. psychrophilum OmpA shows no similarity with any other OMPs of Gramnegative bacteria outside of the family Flavobacteriaceae, we have recently shown that OmpA contains five possible thrombospondin type 3 repeat : OmpA/MotB domains, suggesting that it might be involved in the interaction/ adherence of the pathogen with the host cells, as for other members of the OmpA family (Dumetz et al, 2007). In addition, OmpA is one of the immunodominant antigens, and antibodies raised against it are capable of killing flavobacterial cells in the presence of complement.…”
Section: Immunogenic Omps Of F Psychrophilummentioning
confidence: 99%
See 3 more Smart Citations